Analysis of Effectiveness, Efficiency and Growth in DKI Jakarta Regional Government 2020 – 2022 - Firmansyah; Nanda, Okvia; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
In order to analyze the financial reports in an area, in this case, the regional government of the DKI Jakarta province, it is done by comparing the results achieved from one period to another which uses a number of ratios to report on the realization of the local government budget. The research aims to answer how to analyze the ratio of effectiveness, efficiency and growth in the DKI Jakarta provincial government in 2020-2022. This study uses a qualitative descriptive research method that focuses on the financial performance of the provincial government of DKI Jakarta. The results of this study also concluded that: first, the effectiveness ratio in the period 2020-2022 is classified as effective, which is an average of 94.9%. Second, the efficiency ratio in the 2020-2022 period is classified as inefficient, which is an average of 142.19%.